Examining the donut hole: pandemic housing resilience in three Mid-Atlantic (US) core metro areas - Keith Waters; Terry Clower (Regional Studies, Regional Science)
The COVID-19 pandemic brought an immediate shift to work-from-home, creating differential impacts on regional economies depending on their industrial structure. The increase in work-from-home led planners, researchers and others to hypothesise dramatic changes in housing demand and preferences. This paper examines changes in home sales in the core metro areas of three economically different Mid-Atlantic cities: Baltimore, MD; Washington, DC; and Philadelphia, PA. We use data from the region’s multiple listing service (MLS), Bright MLS, to examine price changes as an indicator of consumer preferences. Descriptive statistics on closed sales prices reveal general price stability related to several key housing characteristics (home type, number of bedrooms, distance to the city centre and location in the metro area) after the onset of the COVID-19 pandemic and subsequent rise in work-from-home. Regression results generally confirm the donut-effect of prices for each of the core metro areas, however, housing market resilience is the most notable overall result. Also notable is that homes with more bedrooms, thought to possibly be used for home offices, have mixed results.